Proposals for the regulation of the South African precious metals industries in the light of domestic and global developments - Damarupurshad, Ashok Kumar (My University, 2016)
The Precious Metals Industry in South Africa is highly-regulated compared with other mining and trading countries in the western world which have either deregulated their precious metals industries, have only partial controls or have never seen the need to regulate gold and platinum-group metals specifically. South Africa has a specific Act of parliament, the Precious Metals Act, 2005 (a modification of Chapter 16 of the Mining Rights Act, 1967), that regulates possession, trading and manufacture of precious metals. Apart from the Russian Federation, no other country in the world regulates gold and platinum-group metals possession, trading and fabrication to the extent still done in South Africa. The requirement for such stringent controls was based on the country’s pre-eminence in the production of gold and platinum over the past fifty years, exchange controls (in the case of gold) and the contribution of gold and platinum-group metals to foreign exchange earnings and to the country’s economy as a whole. However, much has changed in South Africa, in the world and indeed in the precious metals industries domestically and globally and this work is the first attempt to discuss and analyse developments and proposals that are impacting on the regulation of the precious metals industries in South Africa. Of these, the World Gold Council’s Conflict-Free Gold Standard provides a case for industry self- regulation to complement, or substitute for government regulation in future. The hypothesis at the Proposal Stage of this study was that the precious metals industry in South Africa is over-regulated and should be deregulated. In this study, this hypothesis is explored and debated. The Resource Nationalism -motivated proposals, including Producer-Country Price for Platinum, OPEC-type trade bloc for platinum, precious metal exchange and single-channel marketing of platinum, were analysed in this study. It was concluded that these are wanting in terms of cost/benefit or problematic in terms of international agreements and trade and competition laws. iii The Precious Metals Act, 2005 itself was also critically analysed with a view to evaluating what could be regulated better or deregulated in the light of recent developments and proposals. It was found, ironically, that the old problem of illegal mining and trading needs to be brought under control before deregulation of the precious metals industry can begin. Nevertheless, in the run-up to deregulation (in an estimated 10 to 15 years), industry self-regulation, co-regulation (with industry) hallmarking, and a re-examination of how beneficiation is promoted should be considered.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2016
Keywords: Precious metals--Law and legislation--South Africa; Mineral industries--Finance--Law and legislation--South Africa; Mines and mineral resources--South Africa